Forage chain arrangement for sustainable livestock systems in a Mediterranean area. (26th October 2013) - Cosentino, S. L.; Gresta, F.; Testa, G.
Abstract Mediterranean forage systems suffer from limited availability of fresh forage because of water deficits and extreme temperatures. Consequently, fresh forage is unavailable for at least 6–7 months a year, and farmers must buy feed to support livestock production. With the aim of overcoming these limitations, a 2‐year trial was conducted on three distinct sites in Sicily (at 10, 600 and 1200 m elevation) with thirty‐four varieties of forage species belonging to nine biennial/perennial and thirteen annual species. Results showed that by integrating grasses and legumes, species from environments with different climatic conditions enable the season of forage production to be extended from mid‐April to mid‐November. Quality traits of forage in different areas varied in relation to species and varieties. In general, the sown‐forage quality was better than in pastures and fallows in the same areas commonly used to feed animals. This also leads to a reduction in the use of supplementary feeds. Among the tested species, Lolium multiflorum and Medicago sativa emerged as the most promising for filling the forage‐deficit periods, and Trifolium spp. and Vicia sativa were found to be superior for increasing forage quality. The results are discussed in the context of adapting Mediterranean forage supplies for ensuring greater sustainability of livestock production in mountain, hill and plain areas. The proposed forage chain arrangement represents part of local potential adaptation to climate limitations and climate change.